Marine-Derived Bioactive Metabolites as a Potential Therapeutic Intervention in Managing Viral Diseases: Insights from the SARS-CoV-2 In Silico and Pre-Clinical Studies - Queency N. Okechukwu; Feyisayo O. Adepoju; Osman N. Kanwugu; Parise Adadi; Ángel Serrano-Aroca; Vladimir N. Uversky; Charles Odilichukwu R. Okpala (MDPI AG, 2024)
Worldwide urbanization and subsequent migration have accelerated the emergence and spread of diverse novel human diseases. Among them, diseases caused by viruses could result in epidemics, typified by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which hit the globe towards the end of December 2019. The global battle against SARS-CoV-2 has reignited interest in finding alternative treatments for viral infections. The marine world offers a large repository of diverse and unique bioactive compounds. Over the years, many antiviral compounds from marine organisms have been isolated and tested in vitro and in vivo. However, given the increasing need for alternative treatment, in silico analysis appears to provide a time- and cost-effective approach to identifying the potential antiviral compounds from the vast pool of natural metabolites isolated from marine organisms. In this perspective review, we discuss marine-derived bioactive metabolites as potential therapeutics for all known disease-causing viruses including the SARS-CoV-2. We demonstrate the efficacy of marine-derived bioactive metabolites in the context of various antiviral activities and their in silico, in vitro, and in vivo capacities.